PENGARUH SALES PROMOTION, SERVICE QUALITY DAN CUSTOMER EXPERIENCE TERHADAP REPURCHASE INTENTION PADA PENGGUNA LAYANAN SHOPEEFOOD DI KOTA SURABAYA - Christina Whidya Utami; Angeline, Stevi Cris (Universitas Ciputra Surabaya, 2023)
This research is motivated by changes in consumer behavior in terms of shopping for food and beverage products online delivery orders. ShopeeFood is an innovation expansion of Shopee which is an online food and beverage ordering service platform. The existence of ShopeeFood is now being loved by the public as a means of purchasing food online delivery orders, the number of ShopeeFood users has also increased over time, this is known because ShopeeFood has often provided a number of interesting ongoing promotions since its launch. However, the ShopeeFood service is still lagging far behind similar e-commerce platforms that were earlier in the innovation of online food and beverage ordering delivery orders, namely GrabFood and GoFood. This is supported by research by a digital research company in 2021 which shows data on user platforms for ordering food and drinks online delivery orders via ShopeeFood reaching 28% which is still far from competitors like GrabFood at 82% and GoFood at 71%. Therefore, the authors conducted more in-depth research regarding the factors that influence consumer repurchase intention through the ShopeeFood service. This study uses sales promotion, service quality and customer experience variables which represent independent variables that influence the dependent variable, namely repurchase intention for ShopeeFood service users, while the aims of this study are: 1) To find out whether Sales Promotion has an influence on Repurchase Intention on service users ShopeeFood; 2) To find out whether Service Quality has an influence on Repurchase Intention of ShopeeFood service users; 3) To find out whether Customer Experience has an influence on Repurchase Intention of ShopeeFood service users; 4) To find out whether Sales Promotion, Service Quality and Customer Experience simultaneously have an influence on Repurchase Intention of ShopeeFood service users. This research was conducted on a population of people in the city of Surabaya who use ShopeeFood services with the following criteria: 1) Users of ShopeeFood services for more than 3 months; 2) Aged 17 years or over; 3) domiciled in the city of Surabaya; 4) Have made transactions through the ShopeeFood service at least 3 times. Sampling in this study used a purposive sampling technique with a total of 160 respondents.This study uses multiple linear regression analysis with data processing using SPSS, the calculation results show that sales promotion has a significant effect on repurchase intention (Sig. 0.042 <0.05), service quality has a significant effect on repurchase intention (Sig. 0.005 <0.05) ), and customer experience has a significant effect on repurchase intention (Sig. 0.003 <0.05). In addition, this study also shows that sales promotion, service quality and customer experience simultaneously also have a significant effect on repurchase intention (0.000 <0.05).